Effects of asphalt overlay on XCC pile-supported embankment vibration from a moving vehicle - Yin, Feng (2020)
Vibration behaviors of the asphalt pavement-embankment-X-shaped cast-in-situ concrete (XCC) piles reinforced ground system under a moving vehicle are simulated through three-dimensional finite element approach. The influences of asphalt overlays on displacement pattern on the top of pavement, the asymmetric movement of surrounding soil around XCC piles, and the concentration coefficient after laying the overlay are investigated. The obtained results show that the dynamic displacement decreases as a consequence of the increasing stiffness of this system after laying asphalt overlays. It is also shown that the vertical displacement of soil around piles decreases as the thickness of overlays increases. Meanwhile, the asymmetric extent, in which there is an obvious differential displacement between the flat and concave area, is presented. In addition, the concentration coefficient for the embankment's top flat is significantly larger than that for the slope surface, and its increasing is caused by asphalt overlays.